Yaw Angle Tracking Control Design of Underactuated AUV By Using State Dependent Riccati Equations (SDRE)-LQT - Muhammad Basri Hasan (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2019)
In realizing yaw angle control tracking on AUV, the use of the State Dependent Riccati Equations method based on Linear Quadratic Tracking (SDRE-LQT) is realized. This algorithm calculates changes in yaw angle tracking problems through calculation of parameter changes from online AUV with Algebraic Riccati Equations.So that the control signal given to the plant can follow the changing conditions of the plant itself.